Kegunaan Aplikasi Liveworksheet Sebagai LKPD Interaktif Bagi Guru-Guru SD di Masa Pembelajaran Daring Pandemi Covid 19 - L. Heny Nirmayani (Edukasi: Jurnal Pendidikan Dasar, 2022)
The Covid-19 pandemic has had a major impact on various aspects of human life. One of them is in the field of education. As a result of the outbreak, teaching and learning activities that should be carried out face-to-face must now be carried out online. In response to this, the development of learning media, especially those that use technology, is very necessary. Teachers must be more creative and innovative in managing learning activities during the pandemic. One of the interactive worksheets was created using the Liveworksheet application. The Liveworksheet application supports online learning to make it more interesting so that student learning outcomes can be achieved. Liveworksheets can display material in the form of videos, mp3, images, and other interesting symbols that can add interest.